Gorlin Goltz syndrome in childhood: report of two cases. - Procel, C.V.; Aita, V.H.; Sanchez, J.C.; Kiszewski, A.E. (European Journal of Pediatric Dermatology, 2025)
Gorlin Goltz syndrome (GGS), also known as nevoid basal cell carcinoma syndrome, is a rare autosomal dominant disorder with variable expressivity. It is characterized by a predisposition to the development of multiple basal cell carcinomas (BCC), skeletal abnormalities, odontogenic keratocysts, and developmental delay. The aim of this article, which reports two pediatric cases, is to highlight the importance of knowing the particularities of the syndrome in this age group. Although the syndrome is more frequently diagnosed in adulthood, signs such as the sudden appearance of nevoid lesions in photo-exposed and non-photo-exposed areas should suggest this syndrome. Dermoscopic signs are also important, such as the presence of blue-gray globules in the lesions; in larger lesions, arboriform telangiectasias may also be present. It is essential that dermatologists and pediatricians recognize the characteristics of the syndrome for early diagnosis and adequate therapy.